Multicenter study of surgical and oncologic outcomes of extra-levator versus conventional abdominoperineal excision for lower rectal cancer. Issue 1 (January 2020) - Shen, Zhanlong; Bu, Zhaode; Li, Ang; Lu, Junyang; Zhu, Liyu; Chong, Choon Seng; Gao, Zhidong; Jiang, Kewei; Wang, Shan; Li, Fei; Xiao, Yi; Ji, Jiafu; et al.
Abstract: Background: The surgical and oncological outcome of extra-levator abdominoperineal excision (ELAPE) procedure remains unclear in low rectal cancer. Methods: A total of 194 cases of rectal cancer patients underwent ELAPE or conventional abdominoperineal excision (APE) procedure were analyzed in four hospitals' databases from January 2010 to December 2015. Clinicopathological data, overall survival (OS), disease free survival (DFS) and local recurrence free survival (LRFS) of patients were compared between two groups. Results: The operation time spent in perineal phase was significantly shorter in the ELAPE group than that in conventional APE procedure (P < 0.001). There were more specimens with excellent or good quality in ELAPE group compared to conventional APE group (P = 0.033). Patients whom underwent ELAPE procedures showed significantly better OS, DFS and LRFS than those underwent conventional APE procedures. Patients with preoperative stage cT3∼T4 (P = 0.033, P = 0.008, P = 0, 033), cN+ (P = 0.002, P < 0.001, P = 0.006) and pathological stage III-IV (P = 0.023, P = 0.008, P = 0.016) were associated with significant benefits from ELAPE procedure in terms of OS, DFS and LRFS. DFS differed significantly between two groups of patients whom got preoperative chemoradiation therapy (P = 0.009) or postoperative chemotherapy (P = 0.029). For patients of pathological stage IIII-IV without preoperative chemoradiation, ELAPE procedures resulted in statistically better OS (P = 0.018) and DFS (P = 0.030). ELAPE procedure was an independent risk factor of OS, DFS and LRFS in multivariate analysis. Conclusion: Low rectal cancer patients might benefit from ELAPE procedure on both surgical and oncological outcomes, especially in patients with relatively advanced tumors, inspite of the effects of pre-operative radio- and chemotherapy.